On the Boeotian Place Name Θεσπιαί (Minerva, 2019)
According to Pausanias (9,26,6), the Boeotian place name Thespiae (Θεσπιαί) stems either from Thespius (Θέσπιος), the mythic founder of the place, or from Thespia (Θέσπεια), daughter of Asopus. Its lexical basis may be the same as the epic word θέσπις ‘inspired by gods’. The aim of this paper is to examine this hypothetical etymological connexion which has not yet been studied in depth in order to suggest a plausible origin to the place name Θεσπιαί.
Keywords: Thespiae; Toponymy; Mythology; Semantics; θέσπιος